2010
DOI: 10.1007/s00122-010-1358-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping a QTL qCTB7 for cold tolerance at the booting stage on rice chromosome 7 using a near-isogenic line

Abstract: Low temperature at the booting stage is a serious abiotic stress in rice, and cold tolerance is a complex trait controlled by many quantitative trait loci (QTL). A QTL for cold tolerance at the booting stage in cold-tolerant near-isogenic rice line ZL1929-4 was analyzed. A total of 647 simple sequence repeat (SSR) markers distributed across 12 chromosomes were used to survey for polymorphisms between ZL1929-4 and the cold-sensitive japonica cultivar Towada, and nine were polymorphic. Single marker analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 49 publications
2
73
0
Order By: Relevance
“…However, identification of the factors underlying temperature tolerance poses particular challenges. Cool-temperature tolerance in rice appears to be a highly complex trait that involves divergent loci in different rice lines (Takeuchi et al, 2001;Saito et al, 2001;Andaya and Mackill, 2003;Kuroki et al, 2007;Zeng et al, 2009;Saito et al, 2010;Zhou et al, 2010). These quantitative trait loci have been mapped on all twelve chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, identification of the factors underlying temperature tolerance poses particular challenges. Cool-temperature tolerance in rice appears to be a highly complex trait that involves divergent loci in different rice lines (Takeuchi et al, 2001;Saito et al, 2001;Andaya and Mackill, 2003;Kuroki et al, 2007;Zeng et al, 2009;Saito et al, 2010;Zhou et al, 2010). These quantitative trait loci have been mapped on all twelve chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic systems for conferring cool tolerance in rice are not clear, although many quantitative trait loci (QTLs) for cool tolerance at the booting stage have been detected (Takeuchi et al, 2001;Andaya and Mackill, 2003;Ye et al, 2010;Zhou et al, 2010;Kuroi et al, 2011). Saito and his colleagues (2001,2004,2010) have explored QTLs that correlated with cold tolerance of spikelet fertility at the booting stage in rice, and they indicated that an F-box protein gene, located on chromosome 4, is one of the genes conferring cold tolerance based on results from map-based cloning.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of cold-tolerance in rice breeding efforts have focussed on improving seedling vigour, shortening the growth season, and improving cold-tolerance at the booting stage Mackill 2003a, 2003b). Genetic variability has been identified for reproductive stage cold tolerance and this material has made it possible to identify cold-tolerance QTL (Saito et al 2004;Oliver et al 2005;Kuroki et al 2009;Suh et al 2010;Zhou et al 2010). Two cold tolerance loci, Ctb-1 and qCTB7, have been fine-mapped (Saito et al 2004;Zhou et al 2010).…”
Section: Manipulation Of Abiotic Stress Tolerance Using Transgenic Apmentioning
confidence: 99%
“…Genetic variability has been identified for reproductive stage cold tolerance and this material has made it possible to identify cold-tolerance QTL (Saito et al 2004;Oliver et al 2005;Kuroki et al 2009;Suh et al 2010;Zhou et al 2010). Two cold tolerance loci, Ctb-1 and qCTB7, have been fine-mapped (Saito et al 2004;Zhou et al 2010). Breeding for water-logging tolerance is complicated and needs to focus mainly on survival of the below-ground and vegetative plant parts, because the effects on reproductive development are secondary.…”
Section: Manipulation Of Abiotic Stress Tolerance Using Transgenic Apmentioning
confidence: 99%